Lactobacillus brevis CD2 inhibits Prevotella melaninogenica biofilm. (31st October 2013) - Vuotto, C; Barbanti, F; Mastrantonio, P; Donelli, G
<x xml:space="preserve">Abstract</x> Objective To evaluate the ability of the probiotic strain Lactobacillus brevis CD2 to inhibit the opportunistic anaerobe Prevotella melaninogenica (PM1), a well‐known causative agent of periodontitis. Materials and Methods The inhibitory effect of Lactobacillus CD2 on Prevotella PM1 biofilm was assessed both by exposing the anaerobe to the supernatant of the probiotic strain and by growing the two strains to obtain single or mixed biofilms. The inhibitory effect of CD2 on PM1 was also checked by the agar overlay method. Results The development of PM1 biofilm was strongly affected (56% decrease in OD value) by the CD2 supernatant after 96 h. A dose‐dependent biofilm reduction was also observed at 1/10 and 1/100 dilutions of supernatant. Confocal microscopy on the mixed biofilms revealed the ability of CD2 to prevail on PM1, greatly reducing the biofilm of the latter. Conclusions It has been hypothesized a multifactorial nature of the inhibition mechanism, the strong adherence ability of CD2 strain together with the released metabolites presumably contributing to the reduction in the PM1 biofilm detected by confocal microscopy.